Does incident circumcision lead to risk compensation?: evidence from a population cohort in KwaZulu-Natal, South Africa - Ortblad, Katrina; Bärnighausen, Till (Journal of acquired immune deficiency syndromes, 2019)
Background:Voluntary medical male circumcision reduces men's risk of HIV acquisition and may thus increase HIV risk-related sexual behaviors through risk compensation. We analyze longitudinal data from one of Africa's largest population cohorts using fixed-effects panel estimation to measure the eff